Redox status evaluation in dogs affected by mast cell tumour. (24th July 2012) - Finotello, R.; Pasquini, A.; Meucci, V.; Lippi, I.; Rota, A.; Guidi, G.; Marchetti, V.
Abstract Oxidative stress status has been evaluated in depth in human medicine and its role in carcinogenesis has been clearly established. The purpose of this prospective study was to evaluate antioxidant concentrations and oxidative stress in dogs with mast cell tumours (MCTs) that had received no previous treatments, and to compare them to healthy controls. In 23 dogs with mast cell tumour and 10 healthy controls, oxidative status was assessed using the Reactive Oxygen Metabolites‐derived compounds (d‐ROMs) test, antioxidant activity was measured by the Biological Antioxidant Potential (BAP) test, and α‐tocopherol levels were evaluated using high‐performance liquid chromatography and ultraviolet analysis. At baseline, dogs with MCT had significantly higher d‐ROMs (P < 0.00001) and lower BAP (P < 0.0002) compared with healthy controls. However, no significant difference was observed for α‐tocopherol (P = 0.95). Results suggest that oxidative stress pattern and oxidative defence barrier are altered in dogs with newly diagnosed MCT compared with control dogs. Future studies are needed in order to assess the prognostic role of oxidative stress and to evaluate the impact of different therapeutic approaches.